Generation Z Instagram Activism: Between Slacktivism And Online Civic Engagement In Indonesia’s Democracy - Sari, Yunita; Suyato, Suyato; Mulyono, Budi; Murdiono, Mukhamad (Jurnal Pemerintahan dan Politik Lokal, 2025)
This study analyzes how Generation Z's digital activism through Instagram during the August–September 2025 demonstrations reflects substantive civic participation. A mixed-method approach with a sequential explanatory design was used. Quantitative data were analyzed using simple linear regression, and qualitative data were examined through thematic analysis. The study involved 200 Generation Z respondents selected through purposive sampling. The results indicate a statistically significant relationship between Instagram digital activism and online civic engagement (r = 0.818; p < 0.001). Approximately 66.9% of the variation in civic engagement is explained by digital activism. Qualitative findings reveal that Generation Z's digital activism transcends symbolic slacktivism and demonstrates substantive civic participation. Through Instagram features such as Stories, Reels, and templates, they disseminate information, shape public opinion, and coordinate real actions both online and offline. Instagram functions as a strategic medium for reflective and transformative civic engagement, showing that digital participation can evolve into meaningful social movements within the digital democracy ecosystem. Future research should include other social media platforms, expand the sample, and examine digital literacy as a mediating variable.